Vertical tropospheric ozone structure and associated atmospheric transport over the South African Highveld region - Phahlane,Agnes Ngwanakgari. (My University, 2008)
Tropospheric ozone plays an important role in the atmosphere especially towards climate change and air quality. In this study, characteristics of tropospheric ozone over the South African Highveld are investigated using the ozonesonde data collected at Irene weather station (25.9°S, 28.2°E, and 1523 m asl) for the period 1990 to 1993 and 1999 to 2003. It was found that synoptic systems have an effect on the vertical distribution of tropospheric ozone. Ozone stratification appeared during anticyclonic conditions as displayed by a continental high ozone profile. During the ridging high, low ozone concentrations are observed with a strong ozone gradient between 10 and 12 km. Ozone enhancement appeared in the lower altitudes, <4 km, in both the ridging high and the westerly disturbance ozone profiles. Ozone profiles exhibited higher ozone concentrations during the westerly wave conditions. Tropospheric ozone over the South African Highveld region follows a clear annual cycle with lower ozone concentrations observed during autumn and higher ozone concentrations during spring. Summer ozone profiles had high ozone concentrations from the earth’s surface up to 9 km compared to winter ozone profiles. However, winter ozone profiles exhibited higher ozone concentrations than summer ozone profiles and they were characterised by a strong ozone gradient at 12 km. Ozone profiles obtained during the Southern African Fire-Atmosphere Research Initiative conducted in 1992 (SAFARI-92) displayed lower ozone concentrations than ozone profiles from the Southern African Regional Science Initiative conducted during 2000 (SAFARI- 2000). Therefore, it is apparent tropospheric ozone over the South African Highveld has increased over the past decade.
Keywords: Anticyclonic; Tropospheric; Tropopause; Stratosphere; Synoptic